Pemanfaatan Sumber Daya Alam pada Kawasan Rawan Bencana untuk Kegiatan Pariwisata - Finesse Shafina Elwizan; Maya Damayanti (Jurnal Wilayah dan Lingkungan, 2017)
After the eruption of Mount Merapi in 2010, tourism activities in Umbulharjo Village and Kepuharjo Village covered volcano tour, live in, camping and so forth. As the volcano tour grows, the number of visitors has increased but the daily routines of the local community have remained unchanged instead of drastically shifting to the tourism sector. Considering the importance of natural resources for tourism development, the joint utilization of them has created multiple overlapping functionalities. This research aims to assess the utilization of natural resources in disaster-prone areas for tourism activities. The study engaged a descriptive qualitative method with purposive and snowballing methods. The results showed some groupings of natural resources utilization based on the typology of goods and services, the disaster-prone locations, and abundant exploitation in their usage. The proposed management aimed to maintain their sustainable benefits either for supporting the tourism activities or the others.